Mechanism of Swimming Exercise Intervention on Rats with Vascular Dementia Based on PERK/ATF4/CHOP Pathway - LIU Fang; LI Mengxing; WANG Yu; TANG Wei (康复学报)
ObjectiveTo explore the neuroprotective effects of swimming exercise on rats with vascular dementia (VD) based on the PERK/ATF4/CHOP pathway.MethodsA total of 48 male SPF SD rats were randomly divided into sham operation group and experimental group, with 12 and 36 cases respectively. The permanent bilateral common carotid artery occlusion method was used to establish the model in the experimental group, which was randomly divided to model group, swimming exercise group and drug group, with 12 cases in each group. The swimming exercise group underwent load-free swimming training for 30 min/(time·day), lasting for four weeks; the drug group received intraperitoneal injections of monosialotetrahexose ganglioside sodium, 0.33 mg/(kg·day) , lasting for four weeks; the other two groups were allowed free activity for four weeks. After four weeks of intervention, Morris water maze experiment was used to observe behavioral changes of rats; transmission electron microscopy was used to observe the ultrastructure of neurons in the hippocampal CA1 region of rats; real-time fluorescent quantitative PCR (RT-qPCR) and Western blot were used to detect the relative expression levels of protein kinase R-like endoplasmic reticulum kinase (PERK), activating transcription factor 4 (ATF4), and C/EBP homologous protein (CHOP) mRNA and protein.Results(1) Behavioral changes: compared with the sham operation group, the average escape latency in the model group was significantly prolonged, and the number of platform crossing significantly reduced, and the differences were statistically significant (P<0.05). Compared with the model group, the average escape latency of the swimming exercise group and the drug group were significantly shortened, and the number of platform crossing significantly increased (P<0.05). (2) Neuron ultrastructure: in the model group, the number of organelles in the cytoplasm decreased, cytoplasmic matrix dissolution and vacuolization occurred, mitochondria cristae were broken and unclear, and neural fiber necrosis and dissolution were visible; compared with the model group, the swimming exercise group showed significant improvement in the structure of various organelles in the cytoplasm and the degree of vacuolar changes. (3) Expression levers of brain tissue PERK, ATF4, CHOP mRNA and protein: compared with the sham operation group, the expression levels of PERK, ATF4, CHOP mRNA, and protein in the hippocampal CA1 region of the model group significantly increased (P<0.05); compared with the model group, the expression levels of PERK, ATF4, CHOP mRNA and protein in the hippocampal CA1 region of the swimming exercise group significantly decreased (P<0.05).ConclusionSwimming exercise can protect brain tissue in rats with VD and improve their cognitive functions. The mechanism may be related to the regulation of the PERK/ATF4/CHOP pathway, suppressing the expression of ERS-related proteins PERK, ATF4, CHOP mRNA and protein in the hippocampal region of rats with VD.